Analysis of the cost of work absenteeism in nursing personnel - Tipantuña Malte, Paulina (2022)
Objective: to analyze the cost of work absenteeism in nursing personnel of a public Hospital in the city ofSan Luis Potosí, in Mexico. Methodology: retrospective quantitative research through the attendancerecords of the year 2019, 508 people with absenteeism were identified. The cost was determinedbased on the daily salary per shift, estimated for three categories, there were 3,965 absences of which68% correspond to unexcused absences and 31% to medical disability. Results: the estimated annualcost was $ 6,676,134.62 MXN. The groups that presented more absences and therefore generatedmore costs were those corresponding to the month of October, the category of professional nursing,the night shift, in relation to medical disability in January, the unjustified absence presented the highestpeak in the month of October. Conclusion: absenteeism produces high economic costs, which standout in certain groups, by identifying them it is possible to monitor these, and develop strategies thatintervene in the causes that originate it, and thus make timely and pertinent decisions.